2022
DOI: 10.1001/jamaneurol.2021.4161
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Related Imaging Abnormalities in 2 Phase 3 Studies Evaluating Aducanumab in Patients With Early Alzheimer Disease

Abstract: Key Points Question What are the characteristics of amyloid-related imaging abnormalities (ARIA) during aducanumab treatment in individuals with early Alzheimer disease? Findings In an integrated safety data set of 2 phase 3 clinical trials (EMERGE and ENGAGE) including 3285 participants, 425 patients (41.3%) in the combined 10 mg/kg aducanumab group (n = 1029) experienced ARIA; ARIA-edema occurred in 362 patients (35.2%), and 94 of these patients (26.0%) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
324
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(395 citation statements)
references
References 25 publications
6
324
0
4
Order By: Relevance
“…A study by Salloway et al reviewed the clinical and radiographic aspects of ARIA in both EMERGE and ENGAGE trials [ 49 ]. The study found that 425 of 1029 individuals (41.3%) developed ARIA during the placebo-controlled trial period, with 14 patients developing significant events (1.4%) [ 49 ].…”
Section: Studies That Evaluated the Efficacy Or Safety Of Aducanumabmentioning
confidence: 99%
“…A study by Salloway et al reviewed the clinical and radiographic aspects of ARIA in both EMERGE and ENGAGE trials [ 49 ]. The study found that 425 of 1029 individuals (41.3%) developed ARIA during the placebo-controlled trial period, with 14 patients developing significant events (1.4%) [ 49 ].…”
Section: Studies That Evaluated the Efficacy Or Safety Of Aducanumabmentioning
confidence: 99%
“…In the case of aducanumab, the EMA application was submitted 115 days after that to the FDA. This delay may have permitted an application with more mature clinical and safety data, including data from Biogen’s phase III clinical trials showing that 41.3% of patients who received a high dose (10 mg/kg) of aducanumab experienced brain swelling or bleeding compared with 10.3% in the placebo group 16. Furthermore, in 2018 the EMA adopted revised guidelines for the “clinical investigation of medicines for the treatment of Alzheimer's disease.”17,18 This guidance emphasises the need for clinical trials to show cognitive, functional, and global benefit.…”
Section: Different Approachesmentioning
confidence: 99%
“…The study, published in JAMA Neurology ,1 found that the most common ARIA-E or ARIA-H associated symptoms among the 103 symptomatic patients were headache (n=48), confusion (15), dizziness (11), and nausea (8). Among the patients with ARIA-E, most events (98.2%) were resolved radiographically, and 82.8% were resolved within 16 weeks.…”
Section: Symptomsmentioning
confidence: 99%
“…Over 40% of trial participants who had a high dose (10 mg/kg) of the Alzheimer’s disease drug aducanumab experienced brain swelling or bleeding, research has shown 1…”
mentioning
confidence: 99%